Profiling the effects of acne therapeutics, including the novel antibiotic sarecycline, on the human microbiota. Issue 5 (27th May 2022) - Buckley, Anthony; Moura, Ines; Clark, Emma; Altringham, James; Spittal, William; Bentley, Karen; Wilcox, Mark
Abstract : Many factors shape the human intestinal microbiota, some of which can confer a deleterious effect on the microbiota, e.g. antibiotic therapy. Disruption to the microbiota has been implicated in the progression of C. difficile infection (CDI), multiplication of multi-drug resistant organisms and many extra-intestinal diseases. Thus, determining the off-target effects of antibiotics is essential to determine a patient's risk of these diseases, particularly for new therapies. Here we characterise the effect of sarecycline, a novel tetracycline antibiotic for the treatment of moderate to severe acne vulgaris; and compared its effect to the gut microbiota with other acne treatments. Using four independent in vitro gut models, we exposed the human microbiota to either sarecycline, minocycline, doxycycline, or clindamycin, and monitored the changes to the bacterial populations, and whether these changes were sufficient to induce CDI. Sarecycline or doxycycline exposure caused a temporary reduction in the bacterial diversity upon initial exposure. Sarecycline exposure was characterised by a transient increase in Enterococcus spp. and Enterobacteriaceae, and a decrease in Bifidobacterium spp. Doxycycline exposure caused longer-term changes to the Lactobacillaceae and Ruminococcaceae populations. Minocycline exposure resulted in a dramatic reduction to the bacterial diversity, with extensive expansions to the Enterococcus spp. and Enterobacteriaceae populations, whilst the Lactobacillaceae and Ruminococcaceae populations contracted. Whilst clindamycin did induce simulated CDI, neither sarecycline, minocycline, nor doxycycline created a niche conducive for CDI. These data show that long-term sarecycline use has a lower potential for disruption of the colonic microbiota, compared with the current treatments for acne vulgaris.